n-Hexane Bromination Using Barium Fluorobromate Ba(BrF[4])[2]; Procedia Chemistry; Vol. 10 : Chemistry and Chemical Engineering in XXI century - Sobolev V. I. Vasily Igorevich; Radchenko V. B. Vyacheslav Borisovich; Ostvald R. V. Roman Vyacheslavovich; Filimonov V. D. Viktor Dmitrievich; Zherin (Gerin) I. I. Ivan Ignatyevich (2014, 2014)
Title screen